(untitled) (Agroindustrial Science, 2022)
The cultivation and production of grain maize constitute an important opportunity to promote the socio-economic and agricultural development of the communities of Mexico. According to the National Agricultural Planning 2017-2030 related to corn grain proposed by the federal government through the Secretariat of Agriculture and Rural Development (SADER); pointed as a producing region with production potential to the states of Sinaloa, Nayarit, and Jalisco. Grouped by the territorial structure that produces corn grain that predominates in this region. Same that contributed 35% of the national production of this grain in 2021. In order to find significant differences in the yield of corn in water modalities (irrigation and temporal), the analysis of variances for the proposed case of the states that make up the Western Territorial Region is addressed. With a temporality from 2008 to 2018. According to the analysis of variance of a ten-year cohort, it is concluded that in the Western Territory Region it was observed that the average yield of irrigated grain maize production is 1.6 times greater than that of temporary. In the case of Sinaloa, it corresponds to 5.7, in Jalisco to 1.3, and in Nayarit to 1.6 times greater than the irrigation than the storm. This corresponds to and justifies a policy that supports the optimal use of water resources, through irrigation channels or hunting that includes benefits for small producers and not only in agroextractivism.